AN ANALYSIS ON ENGLISH LEARNING MOTIVATION AT THE ELEVENTH GRADE STUDENTS IN SMAN 10 KOTA JAMBI ACADEMIC YEAR 2018/2019 - Ahmady Chandra; Yanti Ismiyati (JELT: Journal of English Language Teaching, 2019)
This study analyzed about extrinsic motivation student in SMA N 10 Kota Jambi. This study is aimed to know about the factor extrinsic motivation student in SMA N 10 Kota Jambi. After giving the questionnaire, the data are analyzed by using a descriptive qualitative research method. The usage of the qualitative is used to know about the extrinsic motivation student in SMA N 10 Kota Jambi. This study can be concluded from 92 students. From the results of questionnaire we know that the largest percentage is student who answered agree and the second largest is students who answered strongly agree, than disagree and strongly disagree. So we can know that extrinsic factors can greatly influence students’ motivation   in learning